Screening of host gut-derived probiotics and effects of feeding probiotics on growth, immunity, and antioxidant enzyme activity of hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂). Issue 136 (May 2023) - Zhu, Yating; Li, Wen; Zhang, Mingqing; Zhong, Zhongxuan; Zhou, Zhiqian; Han, Jiayi; Zhang, Cuiping; Yang, Jinlin; Wu, Yuxin; Shu, Hu
Abstract: In recent years, the widespread use of antibiotics in intensive grouper mariculture has resulted in the ineffectiveness of antibiotic treatment, leading to an increasing incidence of diseases caused by bacteria, viruses, and parasites, causing serious economic losses. Hence, it is crucial to develop alternative strategies to antibiotics for healthy and sustainable development of the mariculture industry. Here, we aimed to screen host gut-derived probiotics and evaluate its effects on growth and immunity of grouper. In this study, 43 bacterial strains were isolated from the intestine of the hybrid grouper ( Epinephelus fuscoguttatus♀ × E. lanceolatus♂ ), and a potential probiotic strain G1-26, which can efficiently secrete amylase, protease, and lipase, was obtained using different screening mediums. Based on 16S rDNA sequencing, the potential probiotic strain G1-26 was identified as Vibrio fluvialis . The results of a biological characteristic evaluation showed that V. fluvialis G1-26 could grow at 25–45 °C, pH 5.5–7.5, salinity 10–40, and bile salt concentration 0–0.030%, and produce amylase, lipase, and protease under different culture conditions. Additionally, V. fluvialis G1-26 is sensitive to many antibiotics and does not exhibit aquatic biotoxicity. Subsequently, hybrid groupers were fed diets containing V. fluvialis G1-26 at different concentrations (0, 10 6, 10 8, and 10 10 CFU/g) for 60 d. The results showed that V. fluvialis G1-26 at 10 8 CFU/g did not significantly affect the growth performance of the hybrid grouper ( P > 0.05). V. fluvialis G1-26 supplementation at 10 8 and 10 10 CFU/g significantly promoted the relative expression of immune-related genes in hybrid groupers ( TLR3, TLR5, IL-1β, IL-8, IL-10, CTL, LysC, TNF-2, and MHC-2 ) and improved the activities of alkaline phosphatase, acid phosphatase, total superoxide dismutase, and total protein in the liver. In conclusion, V. fluvialis G1-26, a potential probiotic strain isolated from the intestine of the hybrid grouper, can be used as an effective immunopotentiator at an optimal dose of 10 8 CFU/g diet. Our results provide a scientific basis for the development and utilization of probiotics in the grouper mariculture industry. Highlights: 43 bacterial strains were isolated from the intestine of the hybrid grouper. A strain G1-26 identified as Vibrio fluvialis with strong digestive enzyme production ability was isolated. The G1-26 feeding at 10 8 and 10 10 CFU/g could enhance the immune performance and the optimal dosage is 10 8 CFU/g diet.